The Translation of Chinese Literature in Spain - Wang, Chenying (Estudios de Traducción, 2016)
In general, Spain is not a country with a strong tradition in Sinology. The translation of Chinese literature in Spain has not yet reached a satisfactory level, and many original works are still ignored. Compared with the translation of Western works, especially with British, French and American literature, the translation of Chinese literature only occupies a tiny quota. In the reception for the Chinese fiction in Spain, indirect translations have played an important role, because Spanish publishing largely depends on other powerful European cultures. This unbalanced situation bespeaks the asymmetrical relations between languages and cultures.